Tingkat Keterdedahan Media Massa dan Perilaku Ber-Kb pada Keluarga Pra-Sejahtera di Pedesaan dan Perkotaan - Asri Sulistiawati; Anna Fatchiya; Aditya Rahmadhony; Diah Puspita Sari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
The service and provision of free family planning (FP) for people belonging to the Pra-Prosperous and Prosperous I is an effort to increase community participation in family planning in order to reduce the TFR figure. In general, this study aims to analyze the behavior of family planning in pre-prosperous and prosperous families, which are divided into two regional characteristics; rural and urban areas. Furthermore, this study seeks to reveal the effect of mass media exposure on behavior change. The research was carried out with a quantitative approach through a survey method which was carried out on 120 households in two different locations: West Bogor District, Bogor City and Gunung Sindur District, Bogor Regency. The results showed that most of the couples of childbearing ages (Pasangan Usia Subur/PUS) had not been exposed to the mass media, especially information regarding family planning. The level of exposure to the mass media did not have a significant effect on changes in the behavior of PUS because respondents still relied on information sourced from extension workers and cadres.